Repetitive transcranial magnetic stimulation (rTMS) using different TMS instruments for major depressive disorder at a suburban tertiary clinic - Maria Cristina Davila; Brianna Ely; Ann M. Manzardo (Mental Illness, 2019)
Repetitive transcranial magnetic stimulation (rTMS) is a neurostimulatory technique used to modulate orbital frontal corticostriatal (OFC) activity and clinical symptomatology for psychiatric disorders involving OFC dysfunction. We examined the effectiveness of rTMS in the treatment of major depressive disorder in an applied clinical setting (Awakening KC CNI) to assess efficacy and optimize rTMS parameters within clinical practice. A retrospective review of medical records was carried out on patients with major depressive disorder undergoing rTMS therapy at Awakenings KC Clinical Neuroscience Institute (CNI), a suburban tertiary psychiatric clinic. A detailed de-identified data set of clinical outcomes was compiled. Patient Health Questionnaire 9 (PHQ-9) total score, clinical remission rate and week achieved were evaluated over 6 weeks of treatment to assess clinical response referencing two different rTMS instruments (MagVenture; NeuroStar). Our survey included 247 participants from males (N=98) and females (N=149) with average baseline PHQ-9 scores of 21.7±4, classified as severe depression. Clinically rated remission rates of 72% were achieved in 3.1±1.0 weeks and associated with prior history of psychiatric hospitalization, suicide attempts and substance use disorder. Average baseline PHQ- 9 scores decreased significantly over time with proportionately greater remission rates achieved for patients treated using the MagVenture over NeuroStar instrument. rTMS in applied clinical practice is efficacious over a wide range of settings and patients. Clinical response was related to severity of depression symptoms (e.g., prior hospitalization; suicide attempts) validating efficacy in critically ill groups. Clinical response may be impacted by rTMS instru- ment, magnetic field parameters or individual factors.